(untitled) (Teología, 2020)
With this article in two parts I hope to open up an examination of the role played by the fourth-century Trinitarian controversies in the late ancient estrangement between Jews and Christians. The article proposes that new partitions emerged in Judaeo-Christiani- ty thanks to the novel practices that during the Trinitarian controversies Christians de- veloped to express their ideas about God. From the viewpoint of theological content, the Trinitarian disputes persisted within a lasting Christian-Jewish continuun: none of the theological options explored by Christians would have caused particular scandal to a contemporaneous Jew on account of its particular articulation of divine reality. Nevertheless, by disengaging from earlier modes of argumentation functioning as bridges between proto-rabbinic and proto-Christian discourses, the production of a theological field on the part of believers in Jesus was largely responsible for the sepa- rate constitution of Christianity and Judaism as intellectual traditions.